2019
DOI: 10.1371/journal.pone.0220380
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography findings in patients with primarily unknown causes of severe or recurrent epistaxis

Abstract: Objective In addition to rhinoscopy, computed tomography of paranasal sinuses (CT) may be performed on patients with primary unknown cause of severe epistaxis (SE) or recurrent epistaxis (RE) to further assess the potential cause of bleeding. The aim of this study was to evaluate CT findings during the work-up of intractable epistaxis patients. Methods 6937 patients were treated in our emergency department with acute epistaxis between 2009–2018. 304/6937 patients underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…CT helps to differentiate among nasal mass and reason of epistaxis in such situation. 6 On the CT scan, a non-enhancing, homogeneous, hypodense, well-defined, rounded, expansile lesion suggestive of mucocele was found. Typically, there is a rim enhancement due to inflammatory and hyperplastic mucosa.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…CT helps to differentiate among nasal mass and reason of epistaxis in such situation. 6 On the CT scan, a non-enhancing, homogeneous, hypodense, well-defined, rounded, expansile lesion suggestive of mucocele was found. Typically, there is a rim enhancement due to inflammatory and hyperplastic mucosa.…”
Section: Discussionmentioning
confidence: 97%
“…There are several causes of epistaxis like trauma, hypertension, bleeding diathesis, nasal tumor, and many more. 1 In cases of unilateral nasal mass in old patients, nasal tumor has to be ruled out. Concha bullosa (CB) is a normal anatomical variant of the middle turbinate in both adults and children.…”
Section: Introductionmentioning
confidence: 99%
“…Epistaxis is one of the most common emergencies in otolaryngology, 1 affecting 12% of the population each year, where around 6% to 10% of these cases require medical treatment in the hospital. 2 Although the majority of nasal bleeding can be treated with conventional local compression, vasoconstrictor and nasal packing; intractable epistaxis cannot be controlled as easily due to the depth of the bleeding site, abnormal nasal anatomy, and uncontrolled persistent bleeding. 3 , 4 Our previous study had found that the responsible arteries for intractable epistaxis are mainly the sphenopalatine artery and the anterior or posterior ethmoidal artery.…”
Section: Introductionmentioning
confidence: 99%